Characterization of the potential new phthalides in Ligusticum chuanxiong Hort. using ultra‐performance liquid chromatography coupled with quadrupole time of flight tandem mass spectrometry. Issue 10 (24th April 2017) - Zhang, Qingqing; Wang, Meiling; Wang, Qing; Zhao, Huizhen; Zhang, Zhixin; Yu, Honghong; Liu, Yuehong; Fu, Shuang; Lu, Zhiwei; Huang, Zhenghai; Xie, Ziye; Gao, Xiaoyan; et al.
Abstract : The characterization of unknown compounds is still a great challenge currently. A strategy for deduction of potential new phthalides through the characterization of isomers based on ultra‐performance liquid chromatography coupled with quadrupole time of flight tandem mass spectrometry was proposed here to characterize the unknown compounds of Ligusticum chuanxiong Hort. (Chuanxiong). This proposed strategy consisted of four steps: (1) the high resolution MS data was collected, and the peaks were screened preliminarily by UNIFI TM platform based on the in‐house database; (2) the fragmentation patterns and the characteristic fragments were summarized based on the representative standards; (3) the target compounds were identified based on the fragmentation rules, standards comparison and false positive exclusion; (4) the unknown components were structurally characterized according to the accurate mass and fragmentation patterns analysis. This strategy was successfully applied to the identification and deduction of phthalides in Chuanxiong. A total of 81 phthalides were detected. Fifty‐five known phthalides were identified, and 26 potential new phthalides were characterized. This research enriched the material basis of Chuanxiong, and provided a liquid chromatography tandem mass spectrometry‐oriented method for the discovery of the potential new compounds.